Pendidikan Karakter pada Peserta Didik di Masa Pandemi Covid-19 Berbasis Keluarga - Setiawan, Agus (Lembaga Penelitian dan Pendidikan Mandala, 2021)
AbstractEducation during the Coronavirus Disease 2019 pandemic has hampered the process of character development for students in schools. The provision of education has been transferred through an online system or study from home, so that the role of the parents is very crucial in supervising and educating their children, especially in instilling character in the family sphere. Character education is very important to learn in order to instill in children so that they can live better and have character with values based on the points of Pancasila’s values. In this study using a literature review approach to review character education in students during pandemic on family-based environment. Parents who are in family institutions serve as the teachers at home and have a strategic role and the main thing is to educate students when learning online at home. Schools, teachers, parents, and the community must work together in an effort to shape the character of students to create harmony in life. Which is why it takes good coordination between parents, teachers, schools, and the community as a supporting factor in order to shape the character of students.Keyword: Character, Students, Family AbstrakPendidikan pada masa Pandemi Covid-19 telah menghambat proses pembentukan karakter peserta didik disekolah. Penyelenggaraan pendidikan telah dialihkan melalui sistem daring (study from home) sehingga peran orang tua sangat sentral dalam mengawasi dan mendidik anak-anaknya terutama dalam menanamkan karakter dalam lingkup keluarga. Pendidikan karakter merupakan pembelajaran yang penting untuk ditanamkan pada anak agar dapat hidup lebih baik dan memiliki karakter dengan nilai-nilai yang berlandaskan sesuai dengan butir-butir pancasila. Dalam studi ini menggunakan pendekatan kajian kepustakaan (literature review) guna mengulas pendidikan karakter pada peserta didik di masa pandemi berbasis keluarga. Orang tua yang berada dalam lembaga keluarga sebagai guru dirumah memiliki peran strategis dan yang utama untuk mendidik peserta didik saat pembelajaran daring dirumah. Sekolah, orang tua, dan masyarakat harus bekerjasama dalam upaya pembentukan karakter peserta didik untuk mewujudkan keharmonisan dalam kehidupan. Sehingga dibutuhkan koordinasi yang baik antara orang tua, sekolah, dan masyarakat sebagai faktor pendukung dalam pembentukan karakter peserta didik.Kata Kunci: Pendidikan Karakter, Peserta Didik, Keluarga